Surfactant‐Assisted Construction of Covalent Organic Frameworks - Youqi Li; Qingqing Zhang; Zhendong Dai; Renzhong Wang; Zhaohua Li; Yu Huang; Runchen Lai; Facai Wei; Feng Shao (Advanced Science)
Abstract Covalent organic frameworks (COFs), characterized by their unique ordered pore structures, chemical diversity, and high degree of designability, have demonstrated immense application potential across multiple fields. However, traditional synthesis methods often encounter challenges such as low crystallinity and uneven morphology. The introduction of surfactants has opened up new pathways for the synthesis of COFs. Leveraging their intermolecular interactions and self‐assembly properties, surfactants can effectively regulate the nucleation, growth processes, and ultimate structure and properties of COFs. This paper systematically reviews the latest research achievements and future trends in surfactant‐assisted COF synthesis, emphasizing the crucial role of surfactants as key additives in the preparation of COFs. Surfactants not only facilitate uniform nucleation and growth of COFs, enhancing the crystallinity and structural order of the products but also enable precise and diverse regulation of the dimensionality, morphology, and structure of COFs. Furthermore, by influencing the dispersion and processability of COFs, surfactants enhance their practicality and workability. Finally, the paper presents some prospects for the challenges and future opportunities in this emerging research area.